How clinical practice is changing the rules: the sunitinib 2/1 schedule in metastatic renal cell carcinoma. Issue 3 (4th March 2017) - Bracarda, Sergio; Negrier, Sylvie; Casper, Jochen; Porta, Camillo; Schmidinger, Manuela; Larkin, James; Gross Goupil, Marine; Escudier, Bernard
ABSTRACT: Introduction : Currently, sunitinib is a standard of care in first-line treatment for metastatic renal cell carcinoma (mRCC). However, with the standard 4/2 schedule (sunitinib 50 mg/day; 4 consecutive weeks on treatment; 2 weeks' rest), 50% of patients require dose reductions to mitigate toxicity, highlighting the need to investigate alternative dosing schedules that improve tolerability without compromising efficacy. Areas covered : We present a concise critical review of published studies comparing the efficacy and safety of the 4/2 and 2/1 schedule (2 weeks on treatment; 1 week rest) for sunitinib. While all studies evaluating the 2/1 schedule have a low level of evidence, the results indicate that the 2/1 schedule improves tolerability compared with the 4/2 schedule, including significant reductions in the incidence of specific adverse events. It was not possible to make any definitive conclusions regarding efficacy due to methodologic limitations of these studies. Expert commentary : In the absence of strong evidence supporting the safety and efficacy of the 2/1 schedule, we recommend that patients should be initiated on sunitinib therapy with the standard 4/2 schedule and only be switched to the 2/1 schedule after the development of dose-limiting toxicities from weeks 3–4 (cycle 1) of the 4/2 schedule cycle.